Improved anti-hepatocellular carcinoma effect by enhanced Co-delivery of Tim-3 siRNA and sorafenib via multiple pH triggered drug-eluting nanoparticles - Chenghua Song; Jia Zhang; Ruichao Wen; Qingshan Li; Jiaxuan Zhou; Xiaoli liu; Zheng Wu; Yi Lv; Rongqian Wu (Materials Today Bio, 2022)
Effective systemic treatment for hepatocellular carcinoma (HCC) remains urgently needed. Sorafenib is the first FDA-approved systemic treatment for HCC. However, individual HCC patents’ response to sorafenib varies greatly. How to enhance the anti-HCC effect of sorafenib is still a significant challenge. T cell immunoglobulin mucin-3 (Tim-3) is a newly identified immune checkpoint molecule and a promising target for HCC treatment. Herein, we developed a novel pH-triggered drug-eluting nanoparticle (CC@SR&SF@PP) for simultaneously delivery of Tim-3 siRNA and sorafenib to HCC in situ. By a single emulsification method, a representative HCC targeted-therapeutic drug sorafenib (SF) was encapsulated into the pH-triggered positive-charged mPEG5K-PAE10K (PP) nanoparticles, followed by condensing of negative-charged Tim-3 siRNA. Then, carboxymethyl chitosan (CMCS), an amphoteric polysaccharide with negative charge in the physiological pH and positive charge in the acidic environment of the tumor, was eventually adsorbed onto the surface of nanoparticles. This co-delivery nanoparticle rapidly and specifically accumulated in the tumor site of the liver and enhanced the targeted, specific and multiple release of siRNA and sorafenib. Enhanced Tim-3 siRNA transfected into tumor cells can not only directly inhibit the growth of tumor cells by knock down the expression Tim-3, but also induce the immune response and enhance the recruitment of cytotoxic T cells to kill tumor cells. The following pH-triggered sorafenib release from SF@PP NPs greatly inhibited the tumor proliferation and angiogenesis, resulting in remarkable tumor growth inhibition in a mouse hepatoma 22 (H22) orthotopic tumor model. Thus, co-delivery of Tim-3 siRNA and sorafenib via this novel pH triggered drug-eluting nanoparticle enhances their anti-tumor efficacy. We expect that such combination treatment strategy will have great potential in future clinical applications.